EFEKTIVITAS PEMBUATAN KARTU TANDA PENDUDUK DIGITAL BERBASIS APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL - Nur, Indri Apriani; Abdi, Abdi; Wahid, Nur (Universitas Muhammadiyah Makassar, 2024)
The aim of the research is to determine the effectiveness of making digital identity cards based on the digital population identity (IKD) application at the Makassar City Population and Civil Registry Service. This type of research uses qualitative methods with descriptive research type, data collection techniques through observation, interviews and documentation. The results of the research show that the implementation of the use of the IKD application has been effective because from the beginning of the implementation of the IKD Application, namely at the end of 2021, the number of people using Digital KTPs was 420 people, then in the middle of 2023 IKD users increased, namely 15,000 people who used IKD, then at the end of 2023 there was a significant increase, namely 50,000 people who used IKD application-based Identity Cards. The IKD application can make things easier for people because people no longer need to queue to make a Digital KTP because the application can be downloaded directly on the Playstore on Android or iPhone cellphones.